PEMIJAHAN IKAN LELE DENGAN TEKNIK PEMIJAHAN ALAM (NATURAL SPAWNING) DAN PEMIJAHAN SEMI ALAMI (INDUCED SPAWNING) - Pungky Slamet Wisnu Kusuma; sukarjati sukarjati; Tony Susilo Wibowo (Jurnal Abadimas Adi Buana, 2019)
The desire of the Sumber Rejeki catfish farmer group to do their own hatchery, but often failures, this causes low income and is not continuous. In addition, the groups of farmers also want to increase their knowledge and skills related to the procedures for spawning catfish naturally and semi-naturally until catfish seeds are ready for sale. The aim of training and mentoring is to find a breakthrough solution for easy-to-use technology to spur gonad maturation, accelerate spawning and mass production of seeds in a continuous and continuous manner with laserpuncture induction technology. Measuring the success of training and mentoring participants can operate the laserpuncture unit correctly, can determine the location of the reproductive acupoint correctly and can induce male and female catfish parents with laserpuncture technology correctly and the catfish parent induced by laserpuncture can mature gonads, quickly spawning and producing catfish seeds in bulk and continuously that are ready for sale.